Linkage mapping of the bovine lysosomal alphamannosidase (MANB) gene - Gelhaus, A.; Hanotte, Olivier H.; Horstmann, R.D.; Teale, A.J. (Wiley, 1999)
Lysosomal alpha-mannosidase is involved in the metabolism of mannoses in oligosaccharides in lysosomes. Deficiency of alpha-mannosidase, alpha-mannosidosis, has been described as an autosomal recessive storage disease in angus cattle, Galloway cattle and in cats. It is caused by non-synonymous substitutions in the encoding gene (MANB). Primers for MANB were designed from a bovine sequence (Gen Bank accession number U97686) and amplified a 316-bp fragment comprising intron 2 and adjacent exonic sequences. This paper discusses PCR primers, PCR conditions and polymorphism detection; and allele frequencies, inheritance and chromosomal location.